Pengaruh Capital Adequacy Ratio dan Loan to Deposit Ratio Terhadap Earning Before Tax pada PT. Bank BJB (Persero), Tbk Periode 2012-2018 - Slamet Wahyuni; Padila Muchtar (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of the Capital Adequacy Ratio and the Loan to Deposit Ratio on Earning Before Tax at PT. Bank BJB (Persero), Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Capital Adequacy Ratio has a significant negative effect on Earning Before Tax by 5.1%, the hypothesis test is obtained t count <t table or (-0.520 <2.571). Loan to Deposit Ratio has a significant negative effect on Earning Before Tax by 12.4%, the hypothesis test is obtained t count <t table or -0.841 <2.571). Capital Adequacy Ratio and Loan to Deposit Ratio simultaneously have a negative but insignificant effect on Earning Before Tax, the regression equation Y = 176,283 - 4,730X1 - 0,132X2 and a determination value of 49.6%, hypothesis testing obtained F value <F table or (1,970 <5,410).